On the Poetics of Irina Polyanskaya’s Story "The Pencil Case" - Stepanov, Aleksandr (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The subject of research is the poetics of Irina Polyanskaya’s story “Penal” (“The Pencil Case”). Deliberations on the specific character of a “feminine mode” of writing (cf. Helene Cixous) usually mention an enhanced physicality, subjectivity, irrationality, nonlinearity, fragmentation, imitation of non-literary forms and limiting the presentation to the private sphere. These characteristics are equally present in the works of many a male author, therefore considering them signs of women’s writing is hardly correct. I am interested in the poetics of the story not as an embodiment of a special, feminine worldview, but as a process of meaning formation, one allowing Polyanskaya to convey individual authorial meanings, including gender-marked ones. I try to trace the semantic dynamics of the key image which is present in the title and which defines the semantic structure of the text. The purpose of the article is to show how the author “works” with the language, with material detail, creating a mature and original work.